The Development of Web-Based Learning Models as A Learning Medium for Students of Audio Video Electronics Competencies - Dedi Hendriana; Rufi'i Rufi'i; Hartono Hartono (Universitas Negeri Malang in collaboration with APSTPI and IPTPI, 2021)
At present distance education has reached almost the entire archipelago. These developments occur a lot in higher education. This benefit is also brought about in secondary education, as seen in SMKN 1 Jetis, especially in the electronics field. Web media with URL ruangpakdedy.com was developed to answer the many electronic learning materials that exist in cyberspace but are still scattered, so the web is made to collect various sources of electronic material in one site. This ease is expected to increase skills that have a greater portion than cognitive knowledge in vocational education. The development used refers to the 4D Thiagarajan model by going through the planning process, material testing by material experts, and media testing by media experts, revisions, products tested on students with good results. As a complement on the web also added assignments that are connected to the LMS page and quiz.